Hank The Cowdog: The Case of the Twisted Kitty - Book 43 - Erickson, John R., 1943-; Holmes, Gerald L. (New York, N.Y. : Puffin Books, 2004)
After getting blamed when Sally May's car ends up in a snowdrift, Hank suspects that this is another plot by Pete the Barncat to get him in trouble.
008-up
Keywords: Dogs -- Fiction; Cats -- Fiction; Ranch life -- Fiction -- West (U.S.); Humorous Stories; West (U.S.) -- Fiction